Digitalization of the Accounts Chamber of the Russian Federation - A. O. Buryakova; A. V. Varnavskii (Управленческие науки)
Due to the analysis of the functioning of the information systems of the Accounts Chamber of the Russian Federation, some problems were found: a substantial part of the accumulated data is outdated and needs clarification, storing data in different formats does not allow analyzing them and others. The key purpose of this work is to identify ways for improving external financial control through the implementation of digital technologies. The research methodology provides for two approaches of the digitalization of state financial control: development of existing information systems to improve their efficiency; creation of a unified digital environment — a digital platform of control bodies based on a transactional approach. According to the results of the study, the authors on the blockchain platform (Hyperledger) created a model of interaction between the Accounts Chamber and the Federal Treasury, the object of the control. On the other hand, the article focuses on the prospects for analysing information in real time, using machine learning. The theoretical and practical significance of the study is to justify the necessity for development a common vision of the functional architecture of solutions proposed by the internal and external financial control authorities.